HRAS overexpression predicts response to Lenvatinib treatment in gastroenteropancreatic neuroendocrine tumors - Liverani, Chiara; Spadazzi, Chiara; Ibrahim, Toni; Pieri, Federica; Foca, Flavia; Calabrese, Chiara; De Vita, Alessandro; Miserocchi, Giacomo; Cocchi, Claudia; Vanni, Silvia; Ercolani, Giorgio; Cavaliere, Davide; et al. (Frontiers in Endocrinology, 2023)
Neuroendocrine neoplasms (NENs) are a rare group of tumors exceptionally heterogeneous, with clinical presentation ranging from well differentiated more indolent tumors to poorly differentiated very aggressive forms. Both are often diagnosed after the metastatic spread and require appropriate medical treatment. A high priority need in the management of this disease is the identification of effective therapeutic strategies for advanced and metastatic patients. The recent TALENT trial demonstrated the efficacy of lenvatinib, a multi-tyrosine kinase inhibitor, in patients with gastroenteropancreatic neuroendocrine tumors (GEP-NETs) with no other treatment indication. Further development of this drug in advanced NETs is warranted. We investigated potential clinical and molecular determinants of lenvatinib response in human primary cultures derived from patients with GEP-NET of different grades and sites of origin. We correlated response to treatment with patient clinical characteristics, with the mutational status of 161-cancer associated genes and with the expression levels of MKI-related genes. Lenvatinib exerted a significant antitumor activity in primary GEP-NET cells, with median survival inhibitions similar or higher than those of standard frontline treatments. Of the 11 primary cultures analyzed in our case series, 6 were classified as responder showing a significant survival inhibition, and 5 as non-responder. We observed that the overexpression of HRAS in the original tumor tissue compared to the matched healthy tissue significantly correlated with responsiveness of primary cells to lenvatinib (p=.048). All 5 non-responder cultures showed normal HRAS expression, while of the 6 responder cultures, 4 had HRAS overexpression. Overexpression of HRAS was not associated with gene mutation. None of the other evaluated clinical variables (grade, Ki67, site of origin and syndromic disease) or molecular markers correlated with response. Lenvatinib appears to be a highly effective drug for the treatment of NETs. The evaluation of HRAS expression in the tumor tissue might improve patient selection and optimize therapeutic outcome.